Conserved Candidate Antigens and Nanoparticles to Develop Vaccine against Giardia intestinalis - Suthinee Sangkanu; Alok K. Paul; Julalak Chuprom; Watcharapong Mitsuwan; Rachasak Boonhok; Maria de Lourdes Pereira; Sonia Marlene Rodrigues Oliveira; Polrat Wilairatana; Mohammed Rahmatullah; Christophe Wiart; Muhammad Nawaz; Chea Sin; et al. (MDPI, 2023)
Giardia intestinalis (Giardia lambia, Giardia duodenalis) infections in humans may be asymptomatic or symptomatic and associated with diarrhea (without blood), abdominal cramps, bloating, flatulence, and weight loss. The protozoan Giardia is the third most common cause of diarrhea and death in children under five, preceded only by rotavirus and by Cryptosporidium parvum and C. hominis infections. Antimicrobial drugs, particularly 5-nitroimidazole (5-NIs), are used to treat giardiasis in humans. Immunologically naive or immunocompromised host are more vulnerable to Giardia infection, whereas a degree of resistance to this protozoan is present in humans living in endemic areas. This suggests that vaccination may be a potential and appropriate means to control this parasitic disease outbreak and protect the human population. This review discusses Giardia antigens related to vaccine development. Additionally, based on the latest development of nanoparticle technology, a combination of methods for future research and development is proposed for the design of the next generation of powerful immunogens and an effective vaccine against Giardia.